An evaluation of operational and research weather forecasts for southern West Africa using observations from the DACCIWA field campaign in June–July 2016. (5th February 2020) - Kniffka, Anke; Knippertz, Peter; Fink, Andreas H.; Benedetti, Angela; Brooks, Malcolm E.; Hill, Peter G.; Maranan, Marlon; Pante, Gregor; Vogel, Bernhard
Abstract: Reliable and accurate weather forecasts, particularly those of rainfall and its extremes, have the potential to improve living conditions in densely populated southern West Africa (SWA). The limited availability of observations has long impeded a rigorous evaluation of current state‐of‐the‐art forecast models. The field campaign of the Dynamics‐Aerosol‐Chemistry‐Cloud Interactions in West Africa (DACCIWA) project in June–July 2016 has created an unprecedentedly dense set of measurements from surface stations and radiosondes. Here we present results from a comprehensive evaluation of both numerical model forecasts and satellite products using these data on a regional and local level. Results reveal a substantial observational uncertainty showing considerable underestimations in satellite estimates of rainfall and low‐cloud cover with little correlation at the local scale. Models have a dry bias of 0.1–1.9  mm · day − 1 in rainfall and too low column relative humidity. They tend to underestimate low clouds, leading to excess surface solar radiation of 43  W · m − 2 . Remarkably, most models show some skill in representing regional modulations of rainfall related to synoptic‐scale disturbances, while local variations in rainfall and cloudiness are hardly captured. Slightly better results are found with respect to temperature and for the post‐onset rather than for the pre‐onset period. Delicate local features such as the Maritime Inflow phenomenon are also rather poorly represented, leading to too cool, dry and cloudy conditions at the coast. Differences between forecast days 1 and 2 are relatively small and hardly systematic, suggesting a relatively quick error saturation. Using explicit convection leads to more realistic spatial variability in rainfall, but otherwise no marked improvement. Future work should aim at improving the subtle balance between the diurnal cycles of low clouds, surface radiation, the boundary layer and convection. Further efforts are also needed to improve the observational system beyond field campaign periods. Abstract : June–July 2016 averaged daily rainfall (mm) from convection‐permitting forecasts using the ICON model (color shading) and station observations (filled circles in same colour scale) over southern West Africa (radiosonde sites shown by red diamonds). The model reproduces the overall pattern of rainfall well but shows a slight underestimation. Four other models are examined in the paper. The models generally struggle to represent local variations in rainfall and cloud but show some skill for regional modulations related to synoptic‐scale disturbances.